INFLUENCE OF LAGER BEER BILLBOARD ADVERTISING ON ATTITUDE AND BEHAVIOUR TOWARDS LAGER BEER CONSUMPTION IN SOUTH EAST NIGERIA - Agboeze, Damian; Chiwoke, Godwin Okoye; Obi, Justina N. (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
In spite of the regulation of alcohol advertising, distribution and consumption, billboard advertising of lager beer brands has become pervasive in South-East, Nigeria. This study examined Influence of Lager Beer Billboard Advertising on Attitude and Behaviour towards Lager Beer Consumption in South East Nigeria. The Explanatory Mixed Method Design was adopted for the study. The population of study was (24, 221, 021.) people. A sample size of six hundred (600.) was drawn from the population. Questionnaire was used to generate quantitative data. Major findings showed that 99% of the respondents were aware that different brands of lager beer exist and could identify them. Flowing from the above, 25.7% of the respondents have high knowledge of different brands of lager beer was influenced by exposure to lager beer billboard advertising’, while, the knowledge of the majority (41.1%) was influenced to a moderate extent. The results indicated a very high exposure to lager beer billboards in South-East Nigeria. Based on these findings, the researchers recommended among others, that; owing to the harmful effects of alcohol and the high rate of its consumption among the audience, the researcher recommends a ban on lager beer and other alcoholic substances advertising. Definitely, this will not stop the consumption of alcohol, but, it can limit the rate at which people are introduced to alcohol. Warning signs on lager beer billboards should be bold and occupy a prominent position for it to command attention. This is because while the majority of the respondents acknowledged their attention to the graphics, message, slogans and icons/celebrities, a significant number of them failed to pay attention to the warnings by the Federal Ministry of Health. Since lager beer consumption is rated +18, it’s suggested that the location of lager beer billboards should be prohibited in areas predominantly occupied by children and adolescents under the age of 18. The findings show that the use of celebrities and high quality graphics received more attention on lager beer billboards than the text/message. Hence, pictures of celebrities accompanied with the brand, should play a prominent role in billboard advertising, especially, as research has shown that people may patronize a product based on the celebrity that endorsed it.